From Mild Cognitive Impairment (MCI) to Dementia in Chronic Obstructive Pulmonary Disease. Implications for Clinical Practice and Disease Management: A Mini-Review - Ranzini, Laura; Schiavi, Mara; Pierobon, Antonia; Granata, Nicolò; Giardini, Anna (Frontiers in Psychology, 2020)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive disease characterized by partially irreversible chronic airflow limitation. Current literature highlights that COPD patients also have an increased risk to develop Mild Cognitive Impairment (MCI) and dementia. Chronic patients with cognitive impairment experience a worsening of health-related quality of life. These patients exhibit difficulties in actively participating in medication adherence and treatment self-management. They also report high levels of anxiety and depression, which are associated with disease severity and poor quality of life. In current literature, there is a lack of studies describing simultaneously the associations between cognitive impairment, dysfunctional psychosocial factors, self-management abilities and their impact on pharmacological/nonpharmacological adherence. The aim of the present short review is to describe the implications of cognitive impairment and psychosocial factors for clinical practice and disease management in COPD patients. Current literature suggests that the assessment of cognitive functioning should be considered in patients with COPD, mainly because different levels of cognitive impairment could affect self-management, adherence and personal independence. Psychosocial factors, such as depression, anxiety, and social support play an important role in adherence to rehabilitation programs and self-management. Due to the impact of the interaction of these factors on adherence to rehabilitation programs, self-management, and rehabilitation completion, future research should investigate simultaneously the role of all these different aspects in order to individuate specific screening tools to evaluate cognitive impairment and psychosocial difficulties. A timely specific evaluation could help to implement a more individualized and personalized treatment.